Sustaining Urban Development in a Post-Conflict Setting: Rebuilding Zamboanga City - Chaves, Carmeli Marie C. (Review of Women's Studies; Vol 26 No 1-2 (2016): Review of Women's Studies Volume XXVI, Numbers 1-2 (January-December 2016), 2023)
This paper examines the urban development pattern of Zamboanga City in Mindanao and describes the post-conflict rehabilitation process among the coastal communities affected by the 2013 siege on the city by the Moro National Liberation Front. The narrative underscores the role of the local community and especially the women in the entire recovery and urban development process as well its efforts to "build back better." Other local government units can learn from the consultative, collaborative approach used in Zamboanga to sustain the development of a socially diverse city.